2021
DOI: 10.1186/s13765-020-00577-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brewer’s spent grain biochar on the growth and quality of leaf lettuce (Lactuca sativa L. var. crispa.)

Abstract: The need for organic soil amendments is increasing in the Republic of Korea against the backdrop of increased soil acidification and nutrient losses. The pyrolysis of biomass produces biochar which not only increases soil productivity but also provides environmental benefits through carbon sequestration. The portion of the brewer’s spent grain (BSG) recycled is by far less than the amount generated, but pyrolysis can help to reverse this trend by turning BSG waste into a valuable soil amendment. The current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 30 publications
(37 reference statements)
0
5
2
Order By: Relevance
“…Additionally, apart from the alkaline biochar + 160 kg/ha N rate and acidic biochar + 320 kg/ha N rate amendments, which produced higher statistically significant EC than the control, the ureaonly amendment led to either higher statistically significant EC than the rest of the biochar amendments or no significant statistically different EC values as compared with the rest of the biochar amendments. These observations contravene those made by several previous studies including those of Lee et al [22], Luyima et al [23,24], Yoo et al [25] and others which indicate that biochar amendments generally increased both the soil pH and EC. The increases in soil pH and EC following biochar application to the soil can been generally attributed to the build-up of ash residues during pyrolysis [26].…”
Section: Chinese Cabbage Yield and Soil Chemical Propertiescontrasting
confidence: 71%
See 1 more Smart Citation
“…Additionally, apart from the alkaline biochar + 160 kg/ha N rate and acidic biochar + 320 kg/ha N rate amendments, which produced higher statistically significant EC than the control, the ureaonly amendment led to either higher statistically significant EC than the rest of the biochar amendments or no significant statistically different EC values as compared with the rest of the biochar amendments. These observations contravene those made by several previous studies including those of Lee et al [22], Luyima et al [23,24], Yoo et al [25] and others which indicate that biochar amendments generally increased both the soil pH and EC. The increases in soil pH and EC following biochar application to the soil can been generally attributed to the build-up of ash residues during pyrolysis [26].…”
Section: Chinese Cabbage Yield and Soil Chemical Propertiescontrasting
confidence: 71%
“…On the other hand, biochar amendments caused no statistically significant differences in the contents of soil cations in comparison with the control experiment. These observations contravene those of Nigussie et al [26], Yoo et al [25] and others who found that biochar amendments increased the concentrations of soil cations. However, a study by Hailegnaw et al [30] assessed the effects of different rates of biochar applied to soils with a wide range of soil physicochemical properties on the contents of soil cations and observed both increments and decrements in the cationic contents.…”
Section: Chinese Cabbage Yield and Soil Chemical Propertiescontrasting
confidence: 63%
“…Root length and leaf length and width were measured with a metre rule. The chlorophyll content was determined using a chlorophyll meter (SPAD-502, Konica Minolta, Tokyo, Japan) as outlined in Yoo et al [27]. Sweetness and NO 3 − N were measured with a digital saccharimeter (HI 96801, Hanna Instruments Inc, Woonsocket, RI, USA) and a NO 3 − N meter (S040, HORIBA Ltd., Kyoto, Japan), respectively, after extraction of the juice out of the leaves.…”
Section: Preparation Of the Compost And Compost And Soil Analysismentioning
confidence: 99%
“…Biochar is a solid, carbon-rich product derived from the thermochemical conversion of biomass (e.g., animal manures, agricultural wastes, wastewater sludge, and other waste products) under oxygen-limited conditions via pyrolysis [4]. Biochar contributes to carbon sequestration, reducing greenhouse gas (GHG) emissions, improving soil properties, and adsorbing organic and heavy metal pollutants [5].…”
Section: Introductionmentioning
confidence: 99%